Effects of a long-term training program of increasing intensity on the immune function of indoor Olympic cyclists - Ferrandez, M. D.; Maynar, M.; De La Fuente, M. (International Journal of Sports Medicine, 1996)
We have studied, on blood samples, the level of immunocompetence (concentration of immune cells, phagocytic process of polymorphonuclear neutrophils, proliferative response of lymphocytes to mitogens), the ascorbic acid content of such immunocompetent cells and the "stress hormone" status (cortisol, ACTH and beta-endorphin) of 10 cyclists, members of the Spanish Indoor Olympic Team and participants in the Olympic Games of Barcelona '92. The study was performed twice during their training for such an event: during the third year of the program (February, 1991) and immediately before the Games (June, 1992). As regards the phagocytic process of neutrophils, we studied the different steps of this process: adherence to endothelium, directed mobility or chemotaxis, ingestion of latex beads and superoxide anion production measured by the nitroblue tetrazolium (NBT) reduction test. We observed a statistically significant increase in chemotaxis and NBT reduction activity just before the Games as compared to the third year of the program, whereas variations were not found in the other parameters. The values of the proliferative capacity of lymphocytes were slightly higher in June '92 than in February '91, but no statistically significant differences were found. The ascorbic acid content decreased strikingly (especially in lymphocytes) immediately before the Games. Regarding the stress hormones and neuropeptides (cortisol, ACTH and beta-endorphin), we observed an increase in serum ACTH and beta-endorphin levels in the last determination (June '92) in comparison to the first one (February '91). These results suggest that, at the end of a long-term training program. no immunosuppression occurs, although an important increase in the concentration of stress hormones (ACTH and beta-endorphin) is found. This is probably caused by the psychological stress associated to the participation in such an important event as the Olympic Games.